Study bioaccumulation of heavy metals Lead (Pb) and Cadmium (cd) in two bivalvia species (Anadara subcrenata Lischke and Meretrix meretrix Linnaeus) from estuarine in Da Nang city - Hong Ha, Pham Thi; Khanh, Nguyen Van; Que, Le Thi (Academia Journal of Biology, 2014)
Bioindicators are species used to monitor the health of an environment or ecosystem. They are any biological species or group of species whose function, population, or status can be used to determine ecosystem or environmental integrity. Bioindicators can tell us about the cumulative effects of different pollutants in the ecosystem and about how long a problem may have been present, which physical and chemical testing cannot. Because almost all toxicity studies are based on the relationship between daily dose and adverse effect, and biomonitoring cannot provide dose information, measured body levels generally cannot be used to assess risk. Thus, the presence of a substance in the body, at any level, cannot be interpreted to mean that adverse effects are likely to occur. Bivalvia are useful and convenient indicators of the ecological health of a waterbody or river. They are almost always present, and are easy to sample and identify. The sensitivity of the range of bivalvia found will enable an objective judgment of the ecological condition to be made. In this study, bioaccumulation of some heavy metals (Pb and Cd) of 2 bivalvia species (Anadara subcrenata Lischke and Meretrix meretrix Linnaeus) was examined in samples collected between January and May, 2008, from estuarine in Da Nang city. Heavy metal contents in tissue were measured by an atomic absorption spectrophometer. The means of the amounts of heavy metals with standard deviation were estimated as follows: 0.51 ± 0.21 - 0.67 ± 0.36 ppm Pb and 0.12 ± 0.03 - 0.21 ± 0.04 ppm Cd (wet weight) for Anadara subcrenata Lischke, but for Meretrix meretrix Linnaeus the means were 1.25 ± 0.24 - 1.59 ± 0.31 ppm Pb and 0.13 ± 0.04 - 0.17 ± 0.05 ppm Cd.